IMPROVING SECONDARY SCIENCE INSTRUCTION THROUGH CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) IN SRI LANKA - Vithanapathirana, Manjula; Nettikumara, Lakshmi (International Online Journal of Education and Teaching, 2020)
There has been a growing interest in incorporating CLIL (Content and Language Integrated Learning) methodology in the Sri Lankan national education system. CLIL refers to methods where subjects, or parts of subjects, are taught through a foreign language to improve both academic subject knowledge and foreign language skills. The 4C's model of Coyle et al (2010) is a popular model for the implementation of CLIL and Sri Lankan system has encouraged using this CLIL model. The main objective of this study was to inquire how CLIL is implemented in secondary science classrooms and to support the teachers. The study was action research. The collaborative action research group comprised a faculty member, a postgraduate research student and ten secondary science teachers from five schools. Arising from the fact-finding needs analysis, the intervention designed included researcher-led teacher workshops to support teachers to plan CLIL lessons. The lessons were implemented in the respective schools by the sample of teachers during school two terms with the support of the researchers. The study concluded that curriculum materials were not focused on CLIL and teachers needed heavy support for content and language integrating for the teaching of science in secondary classes. Preparation of teacher instructional manuals addressing CLIL and in-service teacher development for CLIL lesson planning is recommended.